One Health initiative in India: Genesis and hurdles in establishing the first consortium - Nagendra R. Hegde; Malathi Talari; Subeer S. Majumdar (Veterinary World)
There are several challenges in implementing a meaningful One Health program. These include (a) understanding the language, intricacies, idiosyncrasies, and outcome indicators for each sector in multi-sectoral collaborations, (b) requirement of each partner to be trained outside their area of expertise, (c) absence of analysis of economics and long-term benefits, (d) complexities of the coordination and hand-holding of the various partners, and (e) uninterrupted financing of large consortia. There is, however, a clear understanding of the need for a team effort to support sustainable and progressive development. To achieve such an effort in India, the Department of Biotechnology (DBT), Ministry of Science and Technology, through prolonged deliberation, initiated a One Health project to understand the pervasiveness of the ten most critical zoonotic diseases through a nationwide study of the prevalence of these diseases in animals and to estimate the burden of the same diseases in clinical syndromes encountered in hospital settings. At the end of the project, we hope to map the spread and potential hotspots of the various diseases studied to undertake further collaborative studies focusing on diseases specific to particular geographic locations in the future. This review outlines the One Health initiatives in India and describes the difficulties in implementing the DBT One Health Consortium project.